Integrating SDGs into Islamic Religious Education Curriculum Development for Religious Character Formation - Yusi Tri Hastuti; Meti Fatimah; Nana Abdul Aziz; Njoku Ifeanyi Daniel (Universitas Muhammadiyah Surakarta, 2024)
Objective: This study aims to analyze the implementation of Islamic Religious Education (IRE) curriculum development in shaping students’ religious character at SMPN 3 Sukoharjo, in alignment with Sustainable Development Goals (SDG) 4 (Quality Education) and SDG 16 (Peace, Justice, and Strong Institutions). Theoretical framework: The theoretical framework is grounded in character education theory and Islamic pedagogical principles, emphasizing the role of curriculum and teacher behavior in moral development. Literature review: A review of relevant literature highlights the importance of curriculum-based strategies and educator modeling in fostering religious values among adolescents, yet it also identifies a gap in integrating these practices with global education standards such as the SDGs. Methods: Using a qualitative approach with a case study design, this research involved Islamic religious education teachers as key informants. Data were collected through triangulated methods: in-depth interviews, direct observation, and documentation analysis. The findings reveal that curriculum development is implemented through two major strategies: (1) the structured application of the IRE curriculum across both intracurricular and co-curricular programs, and (2) the embodiment of Islamic values by teachers as moral exemplars in everyday school life. Results: Curriculum content is enriched with school values and integrated with the institutional vision and mission, while character-building is reinforced through daily routines, religious practices, and continuous evaluation. Teacher role modeling significantly contributes to students’ character formation by providing tangible and consistent examples of religious conduct, creating a cohesive educational environment. Implications: The implications of this study emphasize the importance of integrating value-based education into national curricula as a sustainable pathway for character development. This approach not only supports the goals of national education but also contributes to the global agenda for sustainable and inclusive education. Novelty: The novelty of this study lies in its contextualized integration of Islamic education curriculum strategies with SDG frameworks, offering a model for religious character development that is both locally rooted and globally aligned.